Keep out! Join in! Cross-generation communication on the mobile internet in Norway. Issue 4 (1st October 2016) - Nag, Wenche; Ling, Rich; Jakobsen, Mona Hovland
Abstract: In this article we examine how teens in Norway navigate the many options for mediated communication when interacting with parents and grandparents. Drawing on workshop discussions with mid-adolescents, we suggest that there is a digital gap in this cross-generation communication despite high Information and Communication Technology (ICT) penetration in the market. The gap appears to be a manifestation of the social dynamic at play when reshaping the relationship between adolescents and their caregivers. This dynamic includes both centrifugal and centripetal forces. Applying the perspective of relational dialectics, we elaborate on how these forces unfold in the domestication of an increasingly complex set of communication tools referred to as polymedia. The empirical analysis suggests that teens assess the tools differently depending on if it is for interaction with parents or grandparents. This is also related to whether the mediated communication sessions are instrumentally or expressively skewed.